Unified Axiomatics of spaces with maximal Movement Group - Pimenov, R. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. И. Пименов, Единая аксиоматика пространств с максимальной группой движенийR. Pimenovas, Erdvių su judėjimų maksimaline grupe vieninga aksiomatika